Web-Based Case File Management System for Motor Vehicle Theft Crimes - Fiarni, Cut; Yonata, Yosi; Saraswati , Ni Made Villien (Department of Informatics Universitas Islam Indonesia, 2026)
This study addresses the inefficiencies in managing motor vehicle theft case data at the West Java Police Department by developing a web-based file management system. The current manual process, which relies on Microsoft Excel, is prone to human error, data duplication, and reporting delays. Our research introduces a system that automates data categorization, detects data similarities (such as duplicate chassis or engine numbers), and streamlines the verification and validation process, which was previously a time-consuming manual task. By employing object-oriented programming principles, the system accommodates diverse data types and dynamic reporting needs. The system's novelty lies in its specific focus on vehicle theft cases and the integration of a multi-level verification process. User Acceptance Testing (UAT) using the UTAUT model showed high user acceptance, with a behavioral intention of 87.5%, performance expectancy of 84%, and effort expectancy of 82%. This new system significantly improves data accuracy, accelerates reporting, and enhances the overall efficiency of criminal case handling.